The membrane-activity of Ibuprofen, Diclofenac, and Naproxen: A physico-chemical study with lecithin phospholipids (2009)
ABSTRACT: Nonsteroidal anti-inflammatory drugs (NSAIDs) represent non-specific inhibitors of the cycloxygenase pathway of inflammation, and therefore an understanding of the interaction process of the drugs with membrane phospholipids is of high relevance. We have studied the interaction of the NSAIDs with phospholipid membranes made from dimyristoylphosphatidylcholine (DMPC) by applying Fourier-transform infrared spectroscopy (FTIR), Förster resonance energy transfer spectroscopy (FRET), differential scanning calorimetry (DSC) and isothermal titration calorimetry (ITC). FTIR data obtained via attenuated total reflectance (ATR) show that the interaction between DMPC and NSAIDs is limited to a strong interaction of the drugs with the phosphate region of the lipid head group. The FTIR transmission data furthermore are indicative of a strong effect of the drugs on the hydrocarbon chains inducing a reduction of the chain–chain interactions, i.e., a fluidization effect. Parallel to this, from the DSC data beside the decrease of Tm a reduction of the peak height of the melting endotherm connected with its broadening is observed, but leaving the overall phase transition enthalpy constant. Additionally, phase separation is observed, inducing the formation of a NSAID-rich and a NSAID-poor phase. This is especially pronounced for Diclofenac. Despite the strong influence of the drugs on the acyl chain moiety, FRET data do not reveal any evidence for drug incorporation into the lipid matrix, and ITC measurements performed do not exhibit any heat production due to drug binding.